ANALISIS STRATEGI PEMASARAN PRODUK KERAJINAN SOUVENIR MENGGUNAKAN ANALYTICAL NETWORK PROCESS - Ajeng Esa Sherina; Musaddad Alfani (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The souvenir business has a large market opportunity both in Indonesia and abroad. Marketing strategy or product distribution is one of the keys to success in product sales/marketing. The purpose of this study is to analyze clusters and nodes that influence decision making in determining the distribution of hanakreasi product. To support this goal, several criteria were obtained, namely location, visitors, cost, risk, product defects, marketing, and competition. For the product distribution strategy by determining alternative solutions that are considered possible and determining the influence between criteria or between existing alternatives and analyzing the best decisions using the Analytical Network Process (ANP). ANP is a method of making decisions based on multiple criteria or Multiple Criteria Decision Making (MCDM). Based on the results of the analysis using the ANP method with Super Decision Software, the right and best decision making in terms of choosing a product distribution strategy for Hanakreasi is a tourism place with an ideal value of 1 (one).